3D multimodal MRI brain glioma tumor and edema segmentation: A graph cut distribution matching approach. (March 2015) - Njeh, Ines; Sallemi, Lamia; Ayed, Ismail Ben; Chtourou, Khalil; Lehericy, Stephane; Galanaud, Damien; Hamida, Ahmed Ben
Abstract : Highlights: A new algorithm for 3D Multimodal MRI Brain Glioma Tumor and Edema Segmentation. New preprocessing algorithm to segment edema. Comprehensive evaluations/comparisons on the publicly available MICCAI-2012 challenge data set. Comprehensive evaluations/comparisons on the testing MICCAI-2012 challenge data set on virtual skeleton database website. Very competitive performance of the proposed algorithm. Abstract: This study investigates a fast distribution-matching, data-driven algorithm for 3D multimodal MRI brain glioma tumor and edema segmentation in different modalities. We learn non-parametric model distributions which characterize the normal regions in the current data. Then, we state our segmentation problems as the optimization of several cost functions of the same form, each containing two terms: (i) a distribution matching prior, which evaluates a global similarity between distributions, and (ii) a smoothness prior to avoid the occurrence of small, isolated regions in the solution. Obtained following recent bound-relaxation results, the optima of the cost functions yield the complement of the tumor region or edema region in nearly real-time. Based on global rather than pixel wise information, the proposed algorithm does not require an external learning from a large, manually-segmented training set, as is the case of the existing methods. Therefore, the ensuing results are independent of the choice of a training set. Quantitative evaluations over the publicly available training and testing data set from the MICCAI multimodal brain tumor segmentation challenge (BraTS 2012) demonstrated that our algorithm yields a highly competitive performance for complete edema and tumor segmentation, among nine existing competing methods, with an interesting computing execution time (less than 0.5 s per image).